1993
DOI: 10.1128/mcb.13.6.3641
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila erect wing gene, which is important for both neuronal and muscle development, encodes a protein which is similar to the sea urchin P3A2 DNA binding protein.

Abstract: The erect wing (ewg) locus ofDrosophila melanogaster encodes a vital function important for the development of the nervous system and the indirect flight muscles. In In recent years, many genes that participate in the formation of the nervous system have been identified in Drosophila melanogaster by genetic or molecular methods. It is reasonable to suggest that certain genes are important for the differentiation of all neurons, whereas others will be important for the enormous microheterogeneity found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 25 publications
3
81
0
Order By: Relevance
“…In all cases, the responses obtained were indistinguishable from wild type (data not shown). The observed changes in wing posture and flight thus arise from specific defect(s), which could be an alteration in indirect flight muscle function in turn caused by developmental and/or physiological changes (Fleming et al, 1989;DeSimone and White, 1993). The physiological changes could lie in the muscle or in any part of a neural circuit for flight.…”
Section: Flight Deficits In Itpr Mutantsmentioning
confidence: 99%
“…In all cases, the responses obtained were indistinguishable from wild type (data not shown). The observed changes in wing posture and flight thus arise from specific defect(s), which could be an alteration in indirect flight muscle function in turn caused by developmental and/or physiological changes (Fleming et al, 1989;DeSimone and White, 1993). The physiological changes could lie in the muscle or in any part of a neural circuit for flight.…”
Section: Flight Deficits In Itpr Mutantsmentioning
confidence: 99%
“…NRF1 is probably involved in a coordinated response of genes encoding key components of energy metabolism (29, 57), including ALAS (28). Genetic and molecular analyses in Drosophila have demonstrated that erect wing plays an important role in the development of muscle and the nervous system (58,59), two tissues with a very high energetic requirement that demand high mitochondrial activity and therefore require elevated synthesis of respiratory pigments.…”
Section: Cloning and Structure Of The Drosophila Alas Gene-twomentioning
confidence: 99%
“…Previous studies have revealed that Ewg is important for embryonic neuronal development and adult flight muscle formation (DeSimone and White, 1993). However, in ewg mutant embryos, we detect no defects in RP2 motor neuron specification or migration, two well-characterized processes that are dependent on Wingless signaling (Chu-LaGraff and Doe, 1993;Bhat, 2007) (supplementary material Fig.…”
Section: Ewg Facilitates Wingless-dependent Flight Muscle Developmentmentioning
confidence: 48%
“…Both Ewg and Ebd1 are expressed predominantly in muscles and in the nervous system (DeSimone and White, 1993;DeSimone et al, 1996;Koushika et al, 2000;Benchabane et al, 2011). To determine whether Ebd1 and Ewg are expressed in the same subset of cells during different developmental stages, we performed immunostaining experiments using Ebd1 and Ewg antisera in embryos, larvae and pupae.…”
Section: Ewg and Ebd1 Are Expressed In Neurons And Myocytesmentioning
confidence: 99%
See 1 more Smart Citation